The influence of environmental conditions on the distribution and abundance of Sauromatum horsfieldii Miq. at Mount Tapak, Bali - Iryadi, Rajif; Wardhani, Putri Kesuma; Sutomo (Buletin Kebun Raya, 2023)
Sauromatum horsfieldii Miq. (Araceae) is recently recorded from Tapak Mount area, Batukahu Bali Nature Reserve. Ecological studies of this species have not been widely studied. This study aimed to analyze the influence of environmental conditions on the vegetation patterns of S. horsfieldii in Tapak Mount, Bali. The method used was purposive sampling with 69 circular plots of 1 m diameter. Analysis of understorey abundance used the Important Value Index (IVI) and measured the distance between vegetation against slope gradient. The distribution analysis used a multidimensional scaling matrix (NMDS) and the physical effects of the environment and other plants used canonical correspondence analysis (CCA). The results showed four understorey species with the highest IVI in the habitat of S. horsfieldii, namely Ichnanthus pallens (Sw.) Munro ex Benth. (36.17%), Cardamine hirsuta L. (10.32%), Deparia petersenii (Kunze) M.Kato (9.14%), and Diplazium sylvaticum (Bory) Sw. (8.70%). The existence of S. horsfieldii adult individuals affects the number of seedlings and juveniles around it, and the most abundant was at the elevation of 1,310–1,325 m above sea level. The highest abundance was found in the northeast (NE) and southeast (SE) slopes. Soil physical factors, slopes, slope aspects, and soil pH significantly influenced the distribution of this plant. The undergrowth growing together with S. horsfieldii included Cardamine hirsuta L., Dendrocnide stimulans (L.f.) Chew, Lipoblepharis urticifolia (Blume) Orchard, Mikania scandens (L.) Willd., Mitracarpus hirtus (L.) DC., and Pilea sp.